A Dual-SSHC Rectifier With Digital-DCB MPPT for Triboelectric Energy Harvesting - Wenyu Peng; Xinling Yue; Willem D. van Driel; Guoqi Zhang; Sijun Du (IEEE Open Journal of the Solid-State Circuits Society, 2025)
Triboelectric nanogenerator (TENG), advantageous in high energy density and flexibility, is promising as a sustainable energy source but can hardly be used to power edge devices directly due to its high-voltage ac output and varying capacitive impedance. To address it, this work proposes a power-conditioning interface with a fully integrated dual synchronous switch harvesting on capacitors (D-SSHC) rectifier for triboelectric energy extraction. Furthermore, a full digital duty-cycle-based (DCB) maximum power point tracking (MPPT) algorithm is developed to optimize the energy harvesting efficiency with simple implementation and continuous tracking. Designed and fabricated in a 0.18- $μ $ m BCD process, the proposed interface can extract energy at a maximum output voltage of 70 V. According to the measurement results, it achieves 99% MPPT efficiency and an energy extraction improvement of 598% compared to a full-bridge rectifier.